Factors determining the competitiveness of small enterprises operating in local markets with a particular focus on business advice - Stawasz, Edward (Czynniki kształtujące konkurencyjność małych przedsiębiorstw działających na rynkach lokalnych ze szczególnym uwzględnieniem doradztwa biznesowego, 2019)
The aim of the presented paper is to identify the significance of selected determinants of the competitiveness of small innovative enterprises operating in local markets that use business advice. The achievement of this aim required identifying the determinants of the competitiveness of small enterprises (characteristics of managers, characteristics of enterprises) and presenting the motives for as well as the areas and effects of using business advice. The second part of the paper presents the results of empirical research carried out using the CATI technique on a sample of 152 small Polish innovative enterprises operating in local markets and at the same time benefiting from business advice. The conducted research confirms the hypothesis of the significant modifying impact of business advice on the system of the competitiveness determinants of enterprises. Improving the competitiveness of enterprises requires the use of business advice as well as the improvement of the capacity to absorb business knowledge
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 108-116
Keywords: small business; determinants of competitiveness; local markets; business advice; małe firmy; determinanty konkurencyjności; rynek lokalny; daradztwa biznesowe